Sediment resuspension and erosion by vortex rings - Munro, Richard J.; Bethke, N.; Dalziel, S. B. (American Institute of Physics, 2009)
Particle resuspension and erosion induced by a vortex ringinteracting with a sediment layer was investigated experimentally using flow visualization (particle image velocimetry), high-speed video, and a recently developed light attenuation method for measuring displacements in bed level. Near-spherical sediment particles were used throughout with relative densities of 1.2–7 and diameters (d)(d) ranging between 90 and 1600 μm1600 μm. Attention was focused on initially smooth, horizontal bedforms with the vortex ring aligned to approach the bed vertically. Interaction characteristics were investigated in terms of the dimensionless Shields parameter, defined using the vortex-ring propagation speed. The critical conditions for resuspension (whereby particles are only just resuspended) were determined as a function of particle Reynolds number (based on the particle settling velocity and dd). The effects of viscous damping were found to be significant for d/δ<15d/δ<15, where δδ denotes the viscous sublayer thickness. Measurements of bed deformation were obtained during the interaction period, for a range of impact conditions. The (azimuthal) mean crater profile is shown to be generally self-similar during the interaction period, except for the most energetic impacts and larger sediment types. Loss of similarity occurs when the local bed slope approaches the repose limit, leading to collapse. Erosion, deposition, and resuspension volumes are analyzed as a function interaction time, impact condition, and sediment size.